Effect of Local Food-Based Supplementary Feeding on the Nutritional Status of Undernourished Under-Five Children - Rahmiyani Idris; Nadimin; Sitti Sahariah Rowa (Fakultas Kedokteran, Universitas Papua, 2026)
Undernutrition among under-five children remains a major public health concern in Indonesia. Local Food-Based Supplementary Feeding is one of the strategies implemented to improve the nutritional status of undernourished under-five children. This study aimed to analyze the effect of Local Food-Based Supplementary Feeding on changes in the nutritional status of undernourished under-five children in the catchment area of the Marusu Community Health Center. This analytical observational study employed a pre–post approach using secondary data. A total sampling technique was applied, involving 54 under-five children who met the inclusion and exclusion criteria. Changes in nutritional status were analyzed using the Wilcoxon signed-rank test. The results showed that 39 under-five children (72.2%) improved to normal nutritional status, while 15 (27.8%) remained undernourished. The mean z-score increased from −2.49 before the intervention to −1.61 after the intervention, with a statistically significant difference (p = 0.000; p < 0.05). The findings indicate that Local Food-Based Supplementary Feeding was associated with improvements in the nutritional status of undernourished under-five children in the catchment area of the Marusu Community Health Center. Therefore, the Local Food-Based Supplementary Feeding Program should be implemented continuously and integrated with nutrition education and growth monitoring to optimize improvements in the nutritional status of under-five children.